Primary Breast Implant-Associated Squamous Cell Carcinoma: A Proposal for a Better Surgical Approach and Clinical Staging System Based on Tumour Characteristics - de Oliveira-Junior, Idam; Gonzaga, Marina Ignácio; Amirati, Chrissie Casella; Vilela, Natachia Moreira; Wohnrath, Durval Renato; Vieira, René Aloisio da Costa [UNESP] (Springer Nature, 2025)
BackgroundThe literature on squamous cell carcinoma associated with breast implants (BIA-SCC) is scarce and is limited primarily to case reports, nonsystematic and systematic reviews. There is no standard for diagnosis, staging, surgical treatment, or survival analysis. MethodsWe add to the literature the first case of BIA-SCC in Brazil. We also conducted a systematic review of the literature on BIA-SCC and subsequently proposed a clinical/surgical staging system based on disease-free survival (DFS) and overall survival (OS). The new staging system considers not only local invasion but also capsule rupture during surgery and the type of resection. ResultsSurvival and recurrence were evaluated in 17 patients. Nine patients experienced recurrence (mean 5.2 months; range 1–12 months), and six died (mean 8.2 months; range 2–17 months). The three patients who experienced prolonged survival underwent capsule resection, mastectomy, and chest wall resection, and one patient underwent capsulectomy despite the absence of extracapsular extension of the disease. The mean OS was 15.5 months (range 2–96 months), and the mean DFS was 13.5 months (range 0–96 months). The new clinical/surgical staging system had good prognostic value for OS (p < 0.001) and DFS (p < 0.001).ConclusionsSquamous cell carcinoma associated with breast implants has a poor prognosis, making early preoperative diagnosis crucial. Total capsulectomy, without spillage of the contents of the capsule, followed by resection of adjacent tissue, may prevent local recurrence. In clinical-surgical staging, the surgeon should consider not only capsule infiltration but also the possibility of surgical injury and the type of resection.